Cutaneous Diseases among an Aging HIV Cohort, Receiving Care at an Infectious Diseases/Primary Clinic. (4th October 2017) - Tracy, Alexis; O'Neill, Sean; Cadena, Jose; Kowalewski, Catherine; Walter, Elizabeth
Abstract: Background: Since the initial description of HIV/AIDS in the USA, cutaneous manifestations have been important in the diagnosis of the disease, and have been frequently associated with immune dysfunction. We sought to describe current dermatologic manifestations in our HIV seropositive veterans who are greater than 50 years of age and compare these to recent reports in HIV seronegative individuals. Methods: This was a retrospective cohort study performed at the South Texas Veterans Health Care System Immunosuppression Clinic. The aim was to review the charts of older HIV-positive veterans with a minimum age of 50, evaluated from January 1, 2015 to December 31, 2015, to investigate any manifestations of cutaneous pathology, HIV and non-HIV-related, analyze the correlation of the dermatological diagnoses made by the ID physicians and those made by dermatologists, and stratify the findings by age and CD4 counts. Results: Two hundred and Forty-one of the 381 HIV seropositive clinic patients met the criteria (236 males, 5 females), the mean age was 59.95 ± 7.41. The median CD4 count was 446 cell/mm 3 . There were 558 dermatological diagnoses made in the year of 2015, 172 of these were new diagnoses. Of the 38 patients also seen by dermatologists for the presenting skin condition, 57.9% of the diagnoses agreed with the diagnosis from the referring infectious disease provider. Conclusion: Dermatologic manifestations continue to be common in our aging HIV seropositive population. The most common diagnosis was syphilis, reflecting an ongoing epidemic of this disease in this population, followed by more common diagnoses of actinic keratosis, seborrheic keratosis, seborrheic dermatitis and onychomycosis. Comparison within the population of more current dermatologic diagnoses with more remote diagnoses shows fewer dermatologic manifestations of cryptococcosis, chronic herpes simplex, histoplasmosis and Kaposi Sarcoma. Disclosures: All authors: No reported disclosures.